Locating the Albatross in Women’s Political Participation in Sub-Saharan Africa - Ademola-Adeoye, Feyisayo (Locating the Albatross in Women's Political Participation in Sub-Saharan Africa, 2021)
Powerpoint presentation on pilot study done in Nigeria and Kenya
Keywords: Women; Sub-Saharan Africa; Political rights; Political participation; Structural Barriers; Political Barriers; Politics